Mind-wandering in Healthy Aging and Early Stage Alzheimer’s Disease - Gyurkovics, Mate (Neuropsychology, 2017)
OBJECTIVE: The frequency of mind-wandering decreases as a function of age in healthy individuals. One possible explanation is that mind-wandering is a resource-dependent process, and cognitive resources decline with age. The present study provides the first investigation of mind-wandering in the earliest stages of Alzheimer’s disease (AD) to further examine the resource model and discontinuities between healthy aging and AD. METHODS: Three large cohorts completed the Sustained Attention to Response Task (SART): a healthy middle-aged group (mean age = 61.79 ± 5.84 years; N = 270), a healthy older adult group (mean age = 76.58 ± 5.27 years; N = 282), and a group with early stage AD (mean age = 76.08 ± 7.17; N = 77), comparable in age to the second group. RESULTS: Self-reports of mind-wandering during the SART decreased as a function of age, and there was a further decrease in the AD group. All three groups produced faster responses on trials before No-Go errors, suggesting mind-wandering occurred in all cohorts. After No-Go errors, healthy older adults slowed disproportionately compared to middle-aged adults. This was not evident in AD individuals who showed post-error slowing comparable to that in the middle-aged group. CONCLUSIONS: The decreased self-reported mind-wandering in older adults and the further decline in AD are consistent with the cognitive resource account of mind-wandering. Behavioral indices suggest that AD is on a continuum with healthy aging, with the exception of post-error slowing which may suggest performance monitoring deficits in early AD individuals (e.g., lack of error awareness).